The Impact of Remittances on Children Educational Outcome in Indonesia - Pratiwi Indri Hapsari (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2019)
This study investigated the impact of remittances on education outcome of children in the migrant household using cross-sectional data from ongoing longitudinal survey International Family Life Survey fifth wave that collected in 2014. The study controls household’s characteristics and individual characteristics and endogeneity problem using Instrumental Variables estimation. This research using Instrumental Variable Probit Estimation. The remittance is the main variable and the married status, sex category, age of household’s head, household’s head education, and wealth as a control variable. This research finds that remittance has a negative and significant effect on the probability of having higher education on children in migrant households.